Politeness Strategies in Performing Commissive Illocutionary Acts in Joseph R. Biden's Inauguration Speech - Rahmani, Alifia Gresiana; Roselani, Ni Gusti Ayu (Lexicon, 2023)
This research aims to explore the use of politeness strategies in the performance of commissive illocutionary acts in Joseph R. Biden’s inauguration speech. The politeness strategies were classified based on the theory of politeness strategies by Brown and Levinson (1987). The commissive illocutionary acts performed are promise, guarantee, and refusal. The result showed that there are 39 performances of commissive illocutionary acts that are found in the speech. The classification and analysis showed that out of 39 utterances, there are 17 occurrences of bald on record, 10 occurrences of positive politeness, and 12 occurrences of off-record. The result shows that, in delivering his inauguration speech, Biden tends to use the most straightforward way of speaking to issue an act.